2014
DOI: 10.1590/abd1806-4841.20142803
|View full text |Cite
|
Sign up to set email alerts
|

Acquired epidermodysplasia verruciformis in a renal transplant recipient - Case report

Abstract: A 24-year-old male patient, who underwent kidney transplant six years ago due to Lupus nephritis, for the last two years presented asymptomatic erythematous scaly plaques on the abdomen and areas exposed to light. Post-transplantation immunosuppressive medications included prednisone, mycophenolate sodium and sirolimus. The histopathologic features were typical for epidermodysplasia verruciformis. Epidermodysplasia verruciformis is a rare autosomal recessive genodermatosis with increased susceptibility to spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…Medications associated with the development of acquired EV are sirolimus, tacrolimus, bendamustine, cyclosporine, corticosteroids, azathioprine, and other immuno-modifying drugs. [46][47][48][49][50][51] These iatrogenic causes of acquired EV have been reported to occur in the setting of organ transplantation, graft versus host disease, atopic dermatitis, chemotherapy, and systemic lupus erythematosus. [46][47][48][49][50][51] The broad immune impairment caused by these medications can cause a general susceptibility to bacterial and viral infections not specific to EV-HPVs.…”
Section: Acquired Epidermodysplasia Verruciformismentioning
confidence: 99%
“…Medications associated with the development of acquired EV are sirolimus, tacrolimus, bendamustine, cyclosporine, corticosteroids, azathioprine, and other immuno-modifying drugs. [46][47][48][49][50][51] These iatrogenic causes of acquired EV have been reported to occur in the setting of organ transplantation, graft versus host disease, atopic dermatitis, chemotherapy, and systemic lupus erythematosus. [46][47][48][49][50][51] The broad immune impairment caused by these medications can cause a general susceptibility to bacterial and viral infections not specific to EV-HPVs.…”
Section: Acquired Epidermodysplasia Verruciformismentioning
confidence: 99%
“…Acquired EV (aEV) is due to an immunodeficiency secondary to immunosuppressant medications following transplant, infection with HIV, or other diseases such as systemic lupus erythematous, tuberculoid leprosy and Hodgkin lymphoma . The underlying mechanism is believed to be similar to gEV: infected cells are not cleared by the immune system because of defective cell‐mediate immunity, leading first to disseminated hyperkeratotic lesions, and then transformation to SCC and other non‐melanoma skin cancer (NMSC).…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism is believed to be similar to gEV: infected cells are not cleared by the immune system because of defective cell‐mediate immunity, leading first to disseminated hyperkeratotic lesions, and then transformation to SCC and other non‐melanoma skin cancer (NMSC). Although the timing of infection and disease onset in acquired EV is variable after the onset of immunosuppression, approximately 92% of acquired EV patients develop lesions within 5 years . One study has suggested that immunosuppression regimens using azathioprine are potentially higher‐risk for EV‐development than other drug combinations .…”
Section: Introductionmentioning
confidence: 99%
“…5 Other conditions of suppressed cellular immunity have been associated with acquired EV such as systemic lupus erythematosus, 6 GVH disease, 7 atopic dermatitis, 8 and solid organ transplantation such as renal transplantation. 9 The description of acquired EV in immunocompromised hosts suggests the potential role of a specific immune deficiency. A novel classification for the different types of EV subdivides the disease into genetic EV (classic and nonclassic according to the mutations) and acquired EV.…”
mentioning
confidence: 99%